2021
DOI: 10.1155/2021/2408006
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of the Antibacterial and Antioxidant Activities of Some Novel Chloroquinoline Analogs

Abstract: Quinoline heterocycle is a useful scaffold to develop bioactive molecules used as anticancer, antimalaria, and antimicrobials. Inspired by their numerous biological activities, an attempt was made to synthesize a series of novel 7-chloroquinoline derivatives, including 2,7-dichloroquinoline-3-carbonitrile (5), 2,7-dichloroquinoline-3-carboxamide (6), 7-chloro-2-methoxyquinoline-3-carbaldehyde (7), 7-chloro-2-ethoxyquinoline-3-carbaldehyde (8), and 2-chloroquinoline-3-carbonitrile (12) by the application of Vil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…General Procedures in the Synthesis of JD-1 to JD-13 According to step 1, the phosphorous oxychloride (POCl 3 ) was added to the dimethyl formamide (DMF) at 0 ̊C to form a Vilsmei-er reagent and was left for colling at room temperature. The compound N-phenylacetamide (1) was gradually added to the Vilsmeier reagent and was refluxed at 80-90 ̊C for 5 h to yield 2-chloroquinoline-3-carbaldehyde (2) [22,23]. In step 2, the compound 2-chloroquinoline-3-carbaldehyde (2) was added with carbonyldiamide (3) in ethanol and was refluxed at 80-90 °C for 5 h to yield (E)-1-((2-chloroquinolin-3-yl) methylene) urea (4) [ 24,25].…”
Section: Chemistrymentioning
confidence: 99%
“…General Procedures in the Synthesis of JD-1 to JD-13 According to step 1, the phosphorous oxychloride (POCl 3 ) was added to the dimethyl formamide (DMF) at 0 ̊C to form a Vilsmei-er reagent and was left for colling at room temperature. The compound N-phenylacetamide (1) was gradually added to the Vilsmeier reagent and was refluxed at 80-90 ̊C for 5 h to yield 2-chloroquinoline-3-carbaldehyde (2) [22,23]. In step 2, the compound 2-chloroquinoline-3-carbaldehyde (2) was added with carbonyldiamide (3) in ethanol and was refluxed at 80-90 °C for 5 h to yield (E)-1-((2-chloroquinolin-3-yl) methylene) urea (4) [ 24,25].…”
Section: Chemistrymentioning
confidence: 99%
“…In 2021, Abdi and co-workers 79 synthesized chloroquinoline from substituted phenylacetamide using V. H. reagent (DMF-POCl 3 ) at 0 °C for 30 minutes followed by heating the reaction mixture at 105 °C for 22 hours, in average yield. The five different new chloroquinoline derivatives were synthesized using chloroquinoline which displayed anti-bacterial and anti-oxidant activities.…”
Section: Synthesis Of Fused-rings Heterocyclic Compoundsmentioning
confidence: 99%
“…Type IIA DNA topoisomerase involved in several roles such as chromatin condensation, chrom-osome segregation, modulation of topological state of DNA, management of DNA structure, that controlled by hydrolysis, ATP binding and release of inorganic phosphate and ADP [10]. A crucial target for cancer treatment is human DNA topoisomerase II [11]. Studies have revealed that targeting Hsp90 and Type IIA DNA topoisomerase with chemical inhibitors is found to be effective antibiotics, antimicrobial agents.…”
Section: Introductionmentioning
confidence: 99%